PERANCANGAN PERANGKAT LUNAK SISTEM INFORMASI INVENTARIS BASE TRANSCEIVER STATION (BTS) PADA PT.TELKOMSEL NETWORK OPERATION KALBAR - Hasanudin Hasanudin (Jurnal Khatulistiwa Informatika, 2013)
PT. Telkomsel network operation kalbar abstract who have many devices BTS (Base Transceiver Station) require a software which can help an inventory of the devices its BTS. So as to make it easier for companies to list the devices contained in a BTS. The problem faced is how to provide information quickly and in a timely manner and has a high accuracy for generating reports on those devices. For it made a software inventory information system base stations serves as a tool to facilitate the company in the BTS-owned inventory.The research was conducted by examining objects and examine the weaknesses of the existing system, so finding the right solution to solve the existing problems. The method used is descriptive writer, which presents the data and explains what it is, by collecting data through interviews, observation and documentation. The design of this software using Visual Basic 6.0 programming language. Software design results can be used to facilitate the inventory of BTS - BTS owned and improve the accuracy of reports generated.Key words: inventory, design, software